2015
DOI: 10.1039/c5dt00221d
|View full text |Cite
|
Sign up to set email alerts
|

Homopolar dihydrogen bonding in main group hydrides: discovery, consequences, and applications

Abstract: This perspective describes the recent discovery and investigation of homopolar dihydrogen bonding, and focuses on the identification and characterisation of hydride-hydride interactions in compounds of the main group elements. A highlight of this programme has been an appreciation of the important role played by this interaction in the structural and thermochemical properties of these materials, and in the mechanisms through which they release hydrogen. A fuller understanding of this new class of H∙∙∙H interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 90 publications
(152 reference statements)
2
41
0
Order By: Relevance
“…Our conclusions are fully in line with the other, mostly experimental studies, in which the destabilizing role of BH¨¨¨HB interactions were also suggested [68][69][70][71][72]. McGrady and coworkers reported the opposite in their series of recent articles [17,20,21,29]. Due to the fact that such interactions are clearly a matter of debate, in addition, we performed the Interacting Quatum Atoms (IQA) based study for the tetrameric models of LiNMe 2 BH 3 .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Our conclusions are fully in line with the other, mostly experimental studies, in which the destabilizing role of BH¨¨¨HB interactions were also suggested [68][69][70][71][72]. McGrady and coworkers reported the opposite in their series of recent articles [17,20,21,29]. Due to the fact that such interactions are clearly a matter of debate, in addition, we performed the Interacting Quatum Atoms (IQA) based study for the tetrameric models of LiNMe 2 BH 3 .…”
Section: Resultssupporting
confidence: 71%
“…It has been demonstrated that the former feature of ammonia borane crystal originates predominantly from the existence of polar dihydrogen bonds N-H δ`¨¨¨´δ H-B between monomers [11][12][13][14][15][16]. Furthermore, it has been proven that the presence of N-H δ`¨¨¨´δ H-B as well as other non-covalent interactions not only determines the stability, but it can also facilitate various steps of dehydrogenation [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thel ack of BCPs between the outer hydrides can be attributed to the much larger H outer ···H outer distances (Table 1) and is in agreement with the absence of strong magnetic coupling between these hydrides.T he considerable electron density along the H outer ···H center bond paths suggests that such counterintuitive hydride···hydride interactions may be afirst step to hydrogen formation:H À + H À ! [34] As solids,the Ca and Sr hydride clusters decompose at atemperature of 135 8 8C. [34] As solids,the Ca and Sr hydride clusters decompose at atemperature of 135 8 8C.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Significant hydride-hydride interactions including bond paths with bond critical points have been found for the solid-state structure of LiH, but not for NaH. [20,21] Theoretical studies on the decomposition of the rhombic dimers (MH) 2 , M ¼ Li, Na, K, into the elements revealed a more facile H 2 formation for Na and K compared with Li, due to the larger size and poorer orbital overlap with hydrogen for the heavier ions. [20,22] This qualitative trend is in line with the observed decomposition temperatures of the alkali metal hydrides; see Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Theoretical studies on the decomposition of the rhombic dimers (MH) 2 , M ¼ Li, Na, K, into the elements revealed a more facile H 2 formation for Na and K compared with Li, due to the larger size and poorer orbital overlap with hydrogen for the heavier ions. [20,22] This qualitative trend is in line with the observed decomposition temperatures of the alkali metal hydrides; see Table 1. Problematic is the high temperature required for hydrogen release in these lighter hydrides (see Table 1), which is in part a result of the high lattice energies of the lighter MH phases, plus the reversibility of this reaction.…”
Section: Introductionmentioning
confidence: 99%